A tribute to Rudolf Vetschera - Christian Stummer; Ayşegül Engin (Central European Journal of Operations Research, 2021)
On the occasion of the 65th birthday of Prof. Dr. Rudolf Vetschera, colleagues from all over the world contributed their works in order to compile an issue that is meant as a tribute to his achievements, wisdom, and kindness.
Keywords: 650; Operations Research/Decision Theory